Positively charged PVC ultrafiltration membrane via micellar enhanced ultrafiltration for removing trace heavy metal cations. (April 2022) - Yang, Qian; Xie, Yanxin; Zhu, Baoku; Zeng, Yan; Zhou, Hangyue; Ai, Panpan; Chen, Gairong
Abstract: One of the major focuses in the field of sewage is the development of low-pressure driven and high-efficiency filtration membrane, particularly for removing extremely low-concentration heavy metals cations. A new type of polyvinyl chloride (PVC) blended ultrafiltration (UF) membrane was fabricated to reject heavy metal cations (e.g., Cd 2+, Co 2+, Ni 2+, Cu 2+, and Zn 2 + ) from simulated waters using micellar enhanced ultrafiltration (MEUF) in this research. The positively charged PVC UF membrane was fabricated by blending PVC and amphiphilic poly (methyl methacrylate- co- dimethylaminoethyl methacrylate) (PMD) which was in-situ quaternized by methyl iodide (CH3 I), then the PVC/PMD blended membrane was fabricated via nonsolvent induced phase separation (NIPS) process. The membranes' pore morphology, surface chemical compositions, surface charge, water contact angle, mechanical strength and water flux were investigated in detail. The influence of pH, transmembrane pressure, sodium dodecylbenzene sulfonate (SDBS) concentration on the filtration of pure SDBS solution was studied. SDBS was subsequently used as surfactant to remove heavy metal ions by micellar enhanced ultrafiltration (MEUF). For a molar ratio of 40:1 (SDBS: metal cation), the rejection of feed solution containing 10 ppm metal cations (e.g., Cd 2+, Co 2+, Ni 2+, Cu 2+, and Zn 2+ ) surpassed 96% with MEUF method. The results showed that the prepared membrane had low-pressure driven and high-efficiency performance, which provided a potential solution for the high-efficiency removal of trace heavy metals cations.